Current status and associated factors of digital literacy among academic nurse educators: a cross-sectional study - Pan Li; Ronghui Tan; Ting Yang; Lingyao Meng (BMC Medical Education)
Abstract Background In the backdrop of the ongoing global digital revolution in education, the digital literacy of teachers stands out as a pivotal determinant within the educational milieu. This study aims to explore the current status and associated factors of digital literacy among academic nurse educators. Methods A cross-sectional design study utilizing an online questionnaire platform (Wenjuanxing) to collect data from August to October 2023. A total of 157 academic nurse educators members from 10 nursing colleges and universities across 5 provinces in China participated in the study. The digital literacy level of academic nurse educators was evaluated using the self-developed Teacher Digital Literacy Questionnaire. Multiple linear regression analysis was employed to examine the factors associated with the digital literacy of academic nurse educators. Results The average digital literacy score was 125.27 ± 11.41, with the average scores for five dimensions from high to low by rank as follows: digital application (46.73 ± 5.38), digital social responsibility (27.22 ± 3.94), digital awareness (20.28 ± 3.17), professional development (19.88 ± 2.76), and digital technology knowledge and skills (11.16 ± 2.03). Multiple linear regression analysis revealed that age, years of teaching experience, awareness of digital advancements, and use of digital technologies (e.g. ChatGPT) (all p < 0.001) were significantly associated with the level of digital literacy among academic nurse educators. Conclusion Our findings suggest a need to design tailored digital education programs that address different age groups. For younger academic nurse educators, the focus should be on how to incorporate digital technology into their teaching practices to enhance educational diversity. For older academic nurse educators, training should prioritize building confidence in using digital tools and developing foundational digital skills to ensure they can effectively integrate technology into their instructional approaches. Therefore, supporting their needs and enhancing teaching competence towards sustainable nursing digital literacy.